Bankers, bureaucrats, and central bank politics : the myth of neutrality - Adolph, Christopher (New York : Cambridge : Cambridge University Press, 2013)
Adolph illustrates the policy differences between central banks run by former bankers relative to those run by bureaucrats. It introduces a new approach to the politics of money focused on the decisive role played by central bankers themselves.
Includes bibliographical references (p. 319-342) and indexes.
osc 24/10/17
Loans
Keywords: Monetary policy; Banks and banking, Central--Political aspects; Bureaucracy